The role of educational Supervision in raising the efficiency of the teacher. (Journal of Human Sciences, 2022)
The study aimed at identifying the role of educational supervision in raising the efficiency of the teacher and developing the educational process in general, by answering the following questions:What is the role of the educational supervision and what is its importance, and what are its types and its educational experiences?The study dealt with a theoretical framework on the concept of educational supervision and its definition. The development of its stages, its importance and objectives, and what are the obstacles that face applying the educational process in a correct and effective manner in order to achieve the desired results. The study also dealt with a theoretical framework on the concept of educational supervision and the educational teacher and how they are connected to achieve the quality and effectiveness in the educational process from the point of view of some educators and scientists. In the study, the descriptive approach was used to find out about the educational philosophy, its most important features, its effective role, and the scientific mechanisms that can be developed until the desired goal is achieved.The importance of this study lies in the fact that it is an attempt to enrich scientific research in the field of educational supervision, and forming a positive progress towards developing and concerning with it.The study also provided a future vision and proposals to activate the role of educational supervision and educational supervisor, as it is an important tributary of the educational process, one of which is the teacher and educational supervisor.